Building Integrated Photovoltaic (BIPV) in Trentino Alto Adige - Maturi, Laura (Green Energy and Technology, 2018)
This book describes exemplary selected projects carried out in the Trentino-Alto Adige region (Italy) exploring numerous building-integrated photovoltaics (BIPV) systems (i.e. modules, construction system, energy systems). It presents 18 case studies analyzing three aspects of PV integration: aesthetic, energy and technology, with information on decision-making, design process and lessons learnt given for each, along with several pictures, including of general system and architectural details. Based on interviews with architects and engineers, experts from façade/glass manufacturers, energy consultants, BIPV experts, PV installers, electricians, private and public building owners and real estate companies, the book provides a source of inspiration and technical knowledge for architects and engineers towards an increased use of PV in architecture.